In situ study of metal leaching from Pd/Al2O3 induced by K2CO3. Issue 2 (18th December 2019) - Newton, Mark A.; Ferri, Davide; Mulligan, Christopher J.; Alxneit, Ivo; Emerich, Hermann; Thompson, Paul B. J.; (Mimi) Hii, King Kuok
Abstract : In situ quick extended X-ray absorption fine structure spectroscopy (QEXAFS) was employed to study temporally and spatially the leaching of Pd from a heterogeneous catalyst caused by K2 CO3 . Abstract : In situ time- and spatially-resolved quick extended X-ray absorption fine structure spectroscopy (QEXAFS) was employed to study temporally and spatially the leaching of Pd from a heterogeneous catalyst caused by K2 CO3 .